Structure-function relationships in ABCG2: insights from molecular dynamics simulations and molecular docking studies. Issue 1 (December 2017) - Ferreira, Ricardo; Bonito, Cátia; Cordeiro, M.; Ferreira, Maria-José; dos Santos, Daniel
Abstract Efflux pumps of the ATP-binding cassette transporters superfamily (ABC transporters) are frequently involved in the multidrug-resistance (MDR) phenomenon in cancer cells. Herein, we describe a new atomistic model for the MDR-relatedABCG2 efflux pump, also named breast cancer resistance protein (BCRP), based on the recently published crystallographic structure of theABCG5/G8 heterodimer sterol transporter, a member of the ABCG family involved in cholesterol homeostasis. By means of molecular dynamics simulations and molecular docking, a far-reaching characterization of theABCG2 homodimer was obtained. The role of important residues and motifs in the structural stability of the transporter was comprehensively studied and was found to be in good agreement with the available experimental data published in literature. Moreover, structural motifs potentially involved in signal transmission were identified, along with two symmetrical drug-binding sites that are herein described for the first time, in a rational attempt to better understand how drug binding and recognition occurs inABCG2 homodimeric transporters.